2014
DOI: 10.3892/etm.2014.1855
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory effect of microRNA-135a on the Th1/Th2 imbalance in a murine model of allergic rhinitis

Abstract: Allergic rhinitis (AR) is primarily caused by a T helper cell (Th)1/Th2 imbalance. In a murine AR model of a previous study, the serum ovalbumin (OVA)-sIgE concentration was high, whereas microRNA (miR)-135a was lowly expressed in the nasal mucosa. The abnormal expression pattern of miR-135a coincided with highly expressed endogenous factors, including GATA binding protein (GATA)-3 and interleukin (IL)-4, and lowly expressed factors, including T-box expressed in T cells (T-bet) and interferon (IFN)-γ. We hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…Inflammation in any tissue is known to involve the activation of eosinophils and degranulation of MCs, which in turn release a variety of pro-inflammatory mediators that can cause tissue damage [ 2 , 19 , 20 ] and trigger the expression and secretion of various biologically active chemicals [ 3 , 21 , 22 ]. For example, we previously found that stimulation with OVA increases the concentration of interleukin 4 (IL-4) [ 11 ], reflecting the symptoms of an allergic reaction similar to that observed in AR patients. In the present study, we confirmed that OVA increases the infiltration of eosinophils and MCs in the nasal mucosa in addition to increasing the total serum IgE concentration and Th2 cell differentiation in our AR mouse model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inflammation in any tissue is known to involve the activation of eosinophils and degranulation of MCs, which in turn release a variety of pro-inflammatory mediators that can cause tissue damage [ 2 , 19 , 20 ] and trigger the expression and secretion of various biologically active chemicals [ 3 , 21 , 22 ]. For example, we previously found that stimulation with OVA increases the concentration of interleukin 4 (IL-4) [ 11 ], reflecting the symptoms of an allergic reaction similar to that observed in AR patients. In the present study, we confirmed that OVA increases the infiltration of eosinophils and MCs in the nasal mucosa in addition to increasing the total serum IgE concentration and Th2 cell differentiation in our AR mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Our decision to focus on the therapeutic potential of miR-135a stems from our previous work indicating that this miR-135a can specifically bind to GATA-3 and that overexpression of miR-135a in AR mice decreases the mRNA and protein expression of both GATA-3 and IL-4 [ 11 ]. Here, these data were confirmed and we further highlighted the ability of this miR-135a to decrease GATA-3 mRNA and protein expression and increase T-bet mRNA expression in the nasal mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several miRNAs have been demonstrated to influence the development, phenotypical stability and functions of Th2 cells. For example, miR-138 and miR-135a regulate the balance of Th1/Th2 in psoriasis by inhibiting runtrelated transcription factor 3 (RUNX3) expression [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…AR is a common disease that serves as a risk factor for the development of other diseases, such as asthma (2). The symptoms of AR, including nasal congestion, rhinorrhea and sneezing, considerably affect the daily activities, quality of sleep and work productivity of patients (3).…”
Section: Introductionmentioning
confidence: 99%